Polyandry pays off: The effects of multiple mating and number of fathers on morphological traits and survival in clutches of nesting green turtles at Tortuguero - Alfaro-Núñez,Alonzo; Jensen,Michael P.; Abreu-Grobois,F. Alberto (PeerJ PrePrints, 2014)
Despite the long debate of whether or not multiple mating benefits the offspring, studies still show contradicting results. Multiple mating takes time and energy. Thus, if females fertilize their eggs with a single mating, why to mate more than once? We investigated and inferred paternal identity and number of sires in 12 clutches (240 hatchlings) of green turtles (Chelonia mydas) nests at Tortuguero, Costa Rica. Paternal alleles were inferred through comparison of maternal and hatchling genotypes, and indicated multiple paternity in at least 11 of the clutches (92%). The inferred average number of fathers was three (ranging from 1 to 5). This in returns suggests that most females successfully got fecundated by at least three males. Moreover, regression analyses were used to investigate for correlation of inferred clutch paternity with morphological traits of hatchlings fitness (emergence success, length, weight and crawling speed); and size of the mother; and an environmental variable (incubation temperature). We suggest and propose two different comparative approaches for evaluating morphological traits and clutch paternity, in order to infer greater offspring survival. First, clutches coded by the exact number of fathers and second by the exact paternal contribution (fathers who gives greater proportion of the offspring per nest). We found significant differences (P < 0.05) in clutches coded by the exact number of fathers for all morphological traits, where a tendency of higher values in offspring sired by two to three fathers was found. The second approach analysing the paternal contribution showed no significant difference (P > 0.05) for any of the traits. The main conclusion is that multiple mating analysed by the exact number of inferred fathers significantly affects the survival of the offspring regardless of morphological trait measured.
Keywords: polyandry; marine turtles; mating systems; evolution; sperm competition; paternal contribution; population genetics; microsatellites